UPACARA ADAT RAMBU SOLO’: ANTARA GENGSI DAN URGENSI - Septiani, Ghana Aldila, G; Mansur, Mochammad; Saputri, Salsabila Dwi (Paradigma: Jurnal Kajian Budaya, 2024)
Rambu Solo’ is one of the most expensive traditional funerals in the world. This has created a general impression that Rambu Solo’ must always be lavishly performed, although in reality it can be adjusted to the bereaved family’s financial circumstances. This research seeks to explain how Rambu Solo’ can be motivated by both urgency and prestige using Abraham Maslow’s humanistic psychology theory. This research applied the qualitative method. Data were collected by interviewing a traditional leader named Ambe Tawang with the aid of a local interpreter, Baharuddin Palepong, who lived in Lembang Palesan, Tana Toraja, South Sulawesi. After collection, the data were then analyzed, reduced, presented, and verified. This study found that only few people still perform Rambu Solo’ to gain prestige, while most people in Lembang Palesan perform it because of urgency factor, that has been passed down from generation to generation.